Transcranial magnetic stimulation (TMS) protocol on lower limb muscle strength in healthy individuals - Thiago Conceição dos Santos; Rildo Tavares dos Santos; Hudson Renatode Paula Oliveira; Felipe Mendes Barcelos Angeli; Emanuelly Augustada Silva Bispo; Ian Manhoni Bahiense; Walter Gomesda Silva Filho; Guilherme Peixoto Tinoco Areas; Fernando Zanelada Silva Arêas (MethodsX)
This study will investigate the effects of high-frequency Transcranial Magnetic Stimulation (TMS) on lower limb muscle strength, using an isokinetic dynamometer to measure strength changes. The research will involve 50 healthy sedentary male participants aged 18–25, randomized into active and sham groups. The protocol will integrate TMS with surface electromyography (sEMG) to assess muscle activation and enhance accuracy. The aim will be to explore whether TMS can influence peripheral neuromuscular characteristics, improving muscle performance.The protocol will involve a double-blind, randomized design and the use of an isokinetic dynamometer for precise muscle strength measurement. By employing TMS, which enhances cortical excitability, and evaluating muscle performance via controlled assessments, the study will seek to provide reliable pre- and post-intervention data. The study’s sample calculation will ensure adequate statistical power and account for potential attrition, with 50 participants included.This research will have potential clinical applications, particularly for muscle rehabilitation and performance optimization. However, it will face limitations, such as a male-only sample and variability in individual responses to TMS. Despite these challenges, the study's findings could inform future therapeutic strategies for enhancing muscle strength and contribute to advancing TMS applications in both clinical and athletic settings.